Japan Demography Crisis: State Involvement in the Rescue of Keiretsu and the Economy - Fitraya Ramadhanny; Nurdin Nurdin (Riviera Publishing, 2026)
This study examines Japan demographic crisis and its implications for the sustainability of Keiretsu as the core structure of the national economy, focusing on the role of the state in responding to this challenge. Declining birth rates and rapid population ageing have reduced the productive labor force, weakened national productivity, and directly threatening Keiretsu in manufacturing, automotive, and heavy industries. The objective of this research is to analyze how Japan as a developmental state, seeks to preserve and transform Keiretsu through targeted policy interventions. The analytical framework is grounded in developmental state theory, which emphasizes the active role of the state in guiding economic growth, industrial development, and technological innovation through close coordination with the private sector. This study employs a qualitative method with a case study approach, drawing on secondary data including academic literature, international institutional reports, corporate publications, and content analysis of media reports and documentary materials. The findings indicate that the Japanese government has adopted a multifaceted strategy, including extending working age participation, mobilizing elderly and female labor, investing heavily in automation and industrial digitalization, reforming labor market institutions, supporting small and medium sized firms within Keiretsu supply chains, and implementing selective immigration policies. The originality of this research lies in its integrated analysis of demographic crisis and Keiretsu sustainability within a developmental state perspective, demonstrating that Keiretsu survival is inseparable from state-led structural intervention while highlighting the continued adaptability of the developmental state model in addressing contemporary demographic challenges.